Tumor Acquisition for Biomarker Research in Lung Cancer. (3rd July 2014) - Stevenson, Marvaretta; Christensen, Jared; Shoemaker, Debra; Foster, Traci; Barry, William T.; Tong, Betty C.; Wahidi, Momen; Shofer, Scott; Datto, Michael; Ginsburg, Geoffrey; Crawford, Jeffrey; D'Amico, Thomas; et al.
Abstract : The biopsy collection data from two lung cancer trials that required fresh tumor samples be obtained for microarray analysis were reviewed. In the trial for advanced disease, microarray data were obtained on 50 patient samples, giving an overall success rate of 60.2%. The majority of the specimens were obtained through CT-guided lung biopsies ( N = 30). In the trial for early-stage patients, 28 tissue specimens were collected from excess tumor after surgical resection with a success rate of 85.7%. This tissue procurement program documents the feasibility in obtaining fresh tumor specimens prospectively that could be used for molecular testing.